On Designing Prototype Model of “MathWiz” Mobile Application as an AR-Based Learning Media to Improve Students’ Mathematical Proficiency - Hakim, Luki Luqmanul; Salmun, Ahmad; Laila Sulastri, Yayu (CV. Publikasi Indonesia, 2024)
Learning loss is one type of learning crisis, which refers to the loss of previously learned competencies, incomplete learning at the grade level, and the numerous consequences of not mastering learning at each grade level. As a result, attempts can be made to address these issues through advancing information technology, particularly through augmented Reality (AR)-based learning technologies and artificial intelligence with machine learning. This study aims to create and evaluate the effectiveness of the mobile application